Analyzing Movement Densities in AlKarkh Districts: A Comparative Study (Journal of Engineering, 2024)
In recent years, many city centers have experienced severe traffic congestion due to focusing on personal transportation, with cars being the easiest and fastest means of travel. The excessive use of cars has led to neglect of social and environmental aspects, further exacerbating the issue. Historical city centers are particularly affected as they are often commercial hubs with an organic network of roads that increase the difficulty of access and movement. As a result, congestion has intensified, and cars have become the only means of transportation between different parts of the city. This research aims to analyze the effects of traffic congestion in city centers by focusing on a case study of AlKarkh. The study relied on observing and collecting information available at the site, calculating movement densities during peak times on five busy days, and analyzing the data. Additionally, the study compared the results with data from 2014 to assess changes in movement densities. The findings from this research can provide evidence for urban planning that aims to develop the road network in historical city centers and improve transportation policies.